Photonic devices - Liu, Jia-Ming, 1953- (Cambridge, 2005)
A unique textbook covering every major photonic device, and striking a careful balance between theoretical and practical concepts. Devices covered include optical fibers, couplers, electro-optic devices, magneto-optic devices, lasers and photodetectors. Ideal for senior undergraduate and graduate courses, but being device driven it is also an excellent engineers' reference.
Keywords: Optoelectronic devices.; Photonics.; elektronické knihy; electronic books